Electrical and Electronic Equipment Consumption and E-waste Generation in Bangladesh: Temporal and Spatial View - Islam, Md. Zahidul (ABC Journal of Advanced Research, 2019)
Socio-economic and demographic conditions play an important role to determine pattern and magnitude of electrical and electronic equipment (EEE) consumption in Bangladesh. The urban area is considered the potential hot spot of e-waste generation as consumption of EEE is higher here than the rural area due to population concentration, economic wellbeing, and cultural orientation. Bangladesh spends a huge amount on importing EEE every year. The paper is to go into electronic equipment consumption pattern in Bangladesh pointing potential sources of e-waste generation. Data from Bangladesh Bureau of Statistics on ICT use and access by household and individual; World Bank consumption database and other sources are revealed, compiled and processed. District wise data are analyzed and presented using Arc GIS software. The study finds that consumption share of EEE is considerably high in lowest and low-income groups. Population structure is found significant in EEE consumption pattern. According to the study, 15-24 years age group which represents the lowermost segment of population but consume the highest share of ICT in terms of computer, internet and cellphone in Bangladesh. Dhaka is the single uppermost EEE consuming city regarding computer, television, mobile phone, and fridge. Divisional headquarters and some other district headquarters are also fallen in potential e-waste generating zone as they are in top ten EEE consuming districts. The pattern of electrical and electronic equipment consumption influences the type and magnitude of e-waste generation in many ways. So, understanding EEE consumption pattern might be useful as an input to e-waste management planning.